EFEKTIVITAS MEDIA KOMIK PADA PENGETAHUAN DAN SIKAP MENGENAI CUCI TANGAN PADA SISWA SEKOLAH DASAR - Abduh Ridha; Selviana Selviana; Fery Azzwar (Jurnal LINK, 2016)
Washing hands can reduce the number of deaths from diarrhea to 42-47%. Washing hands is also part of the curriculum in primary schools, but still not optimal. Currently the necessary health education attractive and easily understood by children, so that the role of media health is very important, one of which is comic. The purpose of this study was to determine the effect of education through comics on knowledge and attitudes about the importance of handwashing. Research involving elementary students of al Azhar Pontianak as a sample. Hypothesis testing using Wilcoxon formula This study is in a quasi-experimental pre-test or post-test with control group design. Research results prove there is an increased knowledge and attitudes in the experimental group. Based on analysis of statistics on the knowledge obtained p value = 0.000 0.05. For the statistical analysis results obtained attitude p value = 0.000 0.05.